The Effect of Using Multimedia Application in Language Issues to Increase Vocability of Deaf Children Class III SLB B YRTRW Surakarta 2018-2019 - Alfath Nuur Fajar Wahyu Subroto (The Center for Disability Studies and Services Brawijaya University, 2019)
This research aims to the effective use of application multimedia sign language to enhancement vocabulary deaf children class III SLB B YRTRW Surakarta in year 2018/2019. This research use pre-experimental design has the form of one group pretest-posttest design.Â A subject in this research such as 7 children deaf class III in SLB B YRTRW Surakarta 2018/2019 that determined use by surfeited sampling. The instrument research use guide oral test with answer the direct question from the question that given by the Â researcher. Data of research analyzed use by Wilcoxon Sign Rank Test.Based on data analysis that was done, the value of Zhitung = -2,366 with asymp.sig.(2-tailed) is 0,018 that under significance level (p < 0,05). That result shows that application multimedia sign language takes effect to increase vocabulary deaf children class III in SLB B YRTRW Surakarta in year 2018/2019.